Recent Advances on Feasible Strategies for Monoterpenoid Production in Saccharomyces cerevisiae - Gao, Qiyu; Wang, Luan; Zhang, Maosen; Wei, Yongjun; Lin, Wei (Frontiers in Bioengineering and Biotechnology, 2020)
Terpenoids are a large diverse group of natural products which play important roles in plant metabolic activities. Monoterpenoids are the main components of plant essential oils and the active components of some traditional Chinese medicinal herbs. Some monoterpenoids are widely used in medicine, cosmetics and other industries, and are mainly obtained by traditional plant biomass extraction methods. These methods face some problems, such as low efficiency, unstable quality, high cost. Moreover, the traditional production cannot satisfy the growing monoterpenoids demand. The development of metabolic engineering, protein engineering and synthetic biology provides an opportunity to produce large amounts of monoterpenoids eco-friendly using microbial cell factories. This mini-review covers the important functions of plant-derived terpenoids and current monoterpenoids production methods. The monoterpenoids biosynthetic pathways, engineering of key monoterpenoids biosynthetic enzymes, and current yeast monoterpenoids production were summarized. In the future, metabolically engineered yeast provides one possible green and sustainable strategy for monoterpenoids supply.